DEVELOPING A CYCLING SUBSYSTEM AS PART OF A SUSTAINABLE MOBILITY STRATEGY: THE CASE OF GDANSK - Romanika OKRASZEWSKA; Krzysztof GRZELEC; Kazimierz JAMROZ (Scientific Journal of Silesian University of Technology. Series Transport)
Modal share is an important component in developing sustainable transport within a city. In recent years, many cities have set modal share targets for balanced and sustainable transport modes: 30% of public transport and 30% of non-motorized (cycling and walking) modes. Gdansk strategic documents have set similar goals with some actions already taken towards those goals. The cycle network is increasing popular. Gdansk’s cycling infrastructure is more developed than that in other Polish cities. Promotional actions are undertaken each year. Despite that, the share of cycling in the modal split still remains at the low level of 1-3%. The article analyses the case study of Gdansk’s cycling policy and its results. The article summarizes the modal share targets set in Gdansk’s strategic documents, describes the development of its cycle network and promotional campaigns, and presents the volume of bicycle traffic and its share in the city’s modal split. Finally, the article aims to identify the causes behind the low percentage of bicyclists in Gdansk.